2017
DOI: 10.1155/2017/9854083
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Cytotoxic and Apoptotic Potential of a Triterpenoid Saponin (3-O-α-L-Arabinosyl Oleanolic Acid) Isolated fromSchumacheria castaneifoliaVahl in Human Non-Small-Cell Lung Cancer (NCI-H292) Cells

Abstract: Lung cancer is the major cause of cancer death among men. A number of natural compounds have proven to be useful in the treatmet of lung cancer. This study was aimed to determine cytotoxic and apoptotoic effects of a natural compound 3-O-α-L-arabinosyl oleanolic acid (3-O-L-AO) isolated from Schumacheria castaneifolia in non-small-cell lung cancer (NCI-H292) cells. Cytotoxic effects of 3-O-L-AO were determined by Sulforhodamine B (SRB) assay and apoptotic effects were tested by evaluating (a) apoptotsis relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Another study showed crude extract of Neosartorya laciniosa KUFC 7896 and Neosartorya tsunodae KUFC 9213 potentiated doxorubicin tumoricidal activity by increasing Dox accumulation in lung cancer nuclei [ 37 ]. Of note, natural compounds such as curcumin and β-asarone from the Chinese herb Acorus tatarinowii [ 38 , 39 ] have showed their tumoricidal activity by reducing the Wnt/β-catenin signaling pathway, by enhancing current chemotherapeutic drugs, for example, curcumin and phloretin [ 40 , 41 ], and by inducing intrinsic or extrinsic apoptotic pathways, including waltonitone, matrine, oxymatrine, astragalin (kaempferol-3- O -β-d-glucoside), and 3- O -α-l-arabinosyl oleanolic acid from Schumacheria castaneifolia Vahl [ 42 , 43 , 44 , 45 , 46 ]. Some natural compounds’ inhibited growth factor have overcome drug resistance, for example, granulatimide, danorubicin, penicinoline, austocystin D, equol, kaempferol, resveratrol, ellagic acid, and butein [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed crude extract of Neosartorya laciniosa KUFC 7896 and Neosartorya tsunodae KUFC 9213 potentiated doxorubicin tumoricidal activity by increasing Dox accumulation in lung cancer nuclei [ 37 ]. Of note, natural compounds such as curcumin and β-asarone from the Chinese herb Acorus tatarinowii [ 38 , 39 ] have showed their tumoricidal activity by reducing the Wnt/β-catenin signaling pathway, by enhancing current chemotherapeutic drugs, for example, curcumin and phloretin [ 40 , 41 ], and by inducing intrinsic or extrinsic apoptotic pathways, including waltonitone, matrine, oxymatrine, astragalin (kaempferol-3- O -β-d-glucoside), and 3- O -α-l-arabinosyl oleanolic acid from Schumacheria castaneifolia Vahl [ 42 , 43 , 44 , 45 , 46 ]. Some natural compounds’ inhibited growth factor have overcome drug resistance, for example, granulatimide, danorubicin, penicinoline, austocystin D, equol, kaempferol, resveratrol, ellagic acid, and butein [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention of pentacyclic triterpenes on genes involved in the intrinsic mitochondrial apoptotic pathway has been previously reported; the diamine-(PEG)ylated oleanolic acid clearly up-regulated caspase-8, caspase-9, caspase-3, and Bak, and down-regulated Bcl-2 [71]. Conversely, 3-O-α-L-arabinosyl oleanolic acid caused up-regulation of Bax [72]. Similarly, ursolic acid reduced the expression of Bcl-2 and increased the level of the apoptotic protein Bax [73].…”
Section: Compounds 4 and 6 Exhibit In Silico Bcl-xl Inhibitionmentioning
confidence: 86%
“…Subsequently, the apoptosis mechanism of si-MTHFD1 in NCI-H1299 cells was investigated by detecting the apoptosis-related factors, including p53, survivin, Bax, and Bcl-2. Samarakoon et al showed that triterpenoid saponin significantly facilitated the apoptosis of NSCLC cells via enhancing p53 and Bax expression and decreasing survivin levels [ 34 ]. Another study revealed that miR-145 upregulation promoted the apoptosis of NSCLC cells through augmenting the Bax/Bcl-2 ratio [ 35 ].…”
Section: Discussionmentioning
confidence: 99%